PERBANDINGAN PROFITABILITAS INDUSTRI PERBANKAN SYARIAH DAN PERBANKAN KONVENSIONAL MENGGUNAKAN METODE STRUKTUR KINERJA (STUDI KASUS PADA BANK BRI SYARIAH DAN BANK BRI KONVENSIONAL) - Nurul Azmi Nurul; Rizqy Fadhlina Putri Rizqy; Ardhansyah Putra Harahap (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2021)
This study aims to analyze the Comparison of Profitability of the Islamic Banking Industry and Conventional Banking Using the Performance Structure Method (Case Study on Sharia Bank Bri Syariah and Conventional Bri Bank. This study uses a qualitative descriptive approach, aims to determine the Comparison of Profitability of Islamic Banking Industry and Conventional Banking Using the Structure Method). Performance (Case Study on Sharia BRI Bank and Conventional BRI Bank. The subjects in this research are BRI Syariah Bank and Conventional BRI Bank and the object of this research is the income statement of BRI Syariah Bank and Conventional BRI Bank. The analytical technique used is qualitative. the results of the study, it can be concluded that the comparison of profitability between BRI Syariah Banks and Conventional BRI Banks is significantly different.The profitability ratio values ​​obtained by Conventional Banks are greater than the profitability ratio values ​​obtained by conventional banks. lkan Islamic Bank. It can be concluded that Conventional BRI Bank shows better financial performance than Sharia BRI Bank.